Europe’s beating cancer plan & citizens’ engagement – The Manifesto for the right to personalized medicine for cancer patients - Votta, Mariano; Fava, Valeria; Cardillo, Maira (Jour Med Resh and Health Sci, 2021)
As we advance Personalized Healthcare (PHC) across Europe, also thanks to the EU Commission initiatives, such as the Europe’s beating cancer plan and the development of the European Reference Networks (ERNs), it is critical not to lose sight of the patient, and to ensure that PHC is made safe, accessible, and affordable to all: every patient has the right to be treated with the best technology for their specific disease based on their specific situation. Technological developments, the basis of personalized medicine, have made available for many patients new diagnostic and therapeutic options that have often led to a better therapeutic adherence to treatment and a better quality of life. In order to allow personalized medicine to develop its full potential in the coming years in Italy and in the rest of the EU, many challenges will have to be faced within the healthcare sector. From the point of view of civic and patient associations, in the face of changing scenarios, it is essential that citizens are aware of this, know how to assert their rights and are vigilant and the first actors of change. In this context, the “Manifesto for the right to personalized medicine for cancer patients”, wants to intervene in support of patients suffering from cancer, providing an in-depth analysis of the opportunities that the approach to personalized medicine today can represent. Launched in Italy in July 2020 by Cittadinanzattiva, the Manifesto is now brought to the attention of European Institutions, in particular the MEP Interest Group “European Patients’ Rights and Cross-Border Healthcare” by Active Citizenship Network, the EU branch of the Italian NGO.